Effects of enhanced UV-B radiation on the interaction between rice and Magnaporthe oryzae in Yuanyang terrace. Issue 12 (28th October 2019) - Li, Xiang; Huang, Lanlin; He, Yongmei; Xie, Chunmei; Zhan, Fangdong; Zu, Yanqun; Sheng, Jianjun; Li, Yuan
Abstract : This paper illustrates the effects of enhanced UV-B radiation on various stages of interaction (pre-infection, during infection and after infection) between M. oryzae and rice leaves. Abstract : Enhanced ultraviolet–B (UV-B) radiation affected the growth of rice and Magnaporthe oryzae, and changed the interactions between them. Increased UV-B radiation (5.0 kJ m −2 d −1 ) on rice leaves in a Yuanyang terrace was conducted before, during, and after infection of the leaves with Magnaporthe oryzae . The relationship between rice blast and UV-B radiation on the disease resistance of rice and the pathogenicity of M. oryzae was studied, and the effects of enhanced UV-B radiation on the interactions between rice and M. oryzae were analysed. The results indicated the following: (1) enhanced UV-B radiation significantly reduced the rice blast disease index, but as infection progressed, the inhibitory effect of UV-B radiation on the disease was weakened. (2) UV-B radiation treatment before infection with M. oryzae (UV-B + M.) significantly increased the activity of the enzymes related to disease resistance (phenylalanine ammonia lyase, lipoxygenase, chitinase, and β-1, 3-glucanase), and the plants exhibited light-induced resistance. (3) Exposure to UV-B radiation after M. oryzae infection (M. + UV-B) did not induce disease course-related protein (PR) activity, but the content of soluble sugar increased. The osmotic stress caused by pathogenic fungi infection was alleviated by active accumulation of soluble sugar; due to this lack of nutrients, it was difficult for the rice blast fungus to grow. (4) Enhanced UV-B radiation significantly inhibited the production of conidia by M. oryzae, and the expression of the pathogenic genes Chitinase, MGP1, MAGB, and CPKA was significantly downregulated. The pathogenicity of M. oryzae was reduced by UV-B radiation. The resistance of rice leaves was weakened by simultaneous exposure to UV-B radiation and M. oryzae (UV-B/M.). Hence, UV-B radiation can weaken the infectivity of M. oryzae, improve the resistance of traditional rice, and contain the disease.